The facts of causation - Mellor, D. H. (International library of philosophy., 1995)
The Facts of Causation covers all kinds of causing and affecting, of both events and facts; deterministic and indeterministic, mental and physical, transparent and opaque. It shows how the chances a cause gives its effects enable it to explain, be evidence for and a means to them, and why it must precede and be (when immediate) contiguous to them. It explains how we detect causation and what embodies it, and why it entails laws of nature that determine the properties and kinds of facts our world contains. Finally it shows how causation distinguishes time from space, makes it linear, gives it a direction and explains our perception of it.